2020
DOI: 10.1264/jsme2.me19124
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizobia for the Improvement of Soybean Cultivation at Cold Conditions in Central Europe

Abstract: In central Europe, soybean cultivation is gaining increasing importance to reduce protein imports from overseas and make cropping systems more sustainable. In the field, despite the inoculation of soybean with commercial rhizobia, its nodulation is low. In many parts of Europe, limited information is currently available on the genetic diversity of rhizobia and, thus, biological resources for selecting high nitrogen-fixing rhizobia are inadequate. These resources are urgently needed to improve soybean productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 54 publications
(64 reference statements)
3
40
0
Order By: Relevance
“…The demand for soybeans from Europe is increasing, and there is a growing interest by farmers to experiment with the crop (Reckling et al, 2020) and to diversify their cropping systems that are dominated by cereals (Hufnagel et al, 2020). There are studies to identify potent indigenous and commercial Bradyrhizobia inoculants suitable for European conditions (Zimmer et al, 2016;Yuan et al, 2020) and attempt to incorporate soybeans in the no-till cover-crop system (Halwani et al, 2019). However, very little is known about the potential of soybeans in higher latitudes (Lamichhane et al, 2020;Schoving et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for soybeans from Europe is increasing, and there is a growing interest by farmers to experiment with the crop (Reckling et al, 2020) and to diversify their cropping systems that are dominated by cereals (Hufnagel et al, 2020). There are studies to identify potent indigenous and commercial Bradyrhizobia inoculants suitable for European conditions (Zimmer et al, 2016;Yuan et al, 2020) and attempt to incorporate soybeans in the no-till cover-crop system (Halwani et al, 2019). However, very little is known about the potential of soybeans in higher latitudes (Lamichhane et al, 2020;Schoving et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previously introduced strains, subsequently, might remain genetically isolated in soil or may undergo genetic changes to fit the local conditions (Perrineau et al, 2014). Indeed, inoculants are often applied to soils with soybean cultivation history and established SNB (Obaton et al, 2002;Narożna et al, 2015;Yuan et al, 2020). Little is known about the possible influences of the previously introduced SNB on the symbiotic performance of commercial inoculants.…”
Section: Introductionmentioning
confidence: 99%
“…BNF depends on successful nodulation and rhizobial efficiency to fix atmospheric N 2 to ammonia. Previous work to mitigate the effects of low RZT on BNF have focused on identifying cold‐tolerant rhizobia (Kühling, Hüsing, Bome, & Trautz, 2018; Yuan et al, 2020; Zhang, Charles, Driscoll, Prithiviraj, & Smith, 2002; Zimmer et al, 2016). However, the success of rhizobial inoculants can depend on their persistence in the soil and competition with native rhizobia, with local strains better adapted to adverse conditions (Thilakarathna & Raizada, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…HGT is a natural process (Bamba et al 2019), but can be problematic in legume crop fields. Brazil has experienced issues with native rhizobia acquiring inoculant symbiotic genes contributing to the RCP for Soybeans (Barcellos et al 2007) and the same phenomenon has been reported for Soybeans grown in Europe (Yuan et al 2020). Conversely, reports of HGT in Australia have not impacted chickpea production (Elias and Herridge 2015).…”
Section: The Complementary Role Of Sequencingmentioning
confidence: 92%
“…Application of microbiome engineering at an agricultural scale would be extremely difficult, but simplified microbiome engineering can be used on a site-by-site basis to identify context dependent contributors to the RCP (Vessey 2004). For example, a rhizobia strain was isolated from a field in Germany that provides greater benefit to Soybean than an elite inoculant at near freezing temperatures (Yuan et al 2020). This suggests that beneficial rhizobia were already present in this soil, and microbiome engineering could be used to determine if, and how, the soil community could be shaped by Soybeans to enhance growth and seed pod production in cold conditions.…”
Section: Concluding Thoughts and Future Directionsmentioning
confidence: 99%